Semen Parameters Changes in Adolescents With Clinical Varicocele after Magnified Subinguinal Varicocelectomy: A Prospective Controlled Study. Issue 6 (December 2022) - Shebl, Salah E.; Sabry, Khaled
Background: Previously, we highlighted the benefits of magnified subinguinal varicocelectomy over conservative treatment on the semen of a small group of adolescents with varicoceles. In this report, we presented changes of semen parameters of 47 adolescents who underwent magnified subinguinal varicocelectomy (MSV) and followed-up for 6 months. Methods: The present prospective controlled study was conducted on 47 adolescents with varicocele who underwent MSV and were followed up for 6 months. In addition, age and sex-matched patients were added as control group. The primary outcome of this study was to assess the postoperative change in semen analysis parameters. Results: A significant increase in sperm volume from 2.5 (1.9–3) to 3.2 (2.6–4) mL at the end of the sixth month of follow-up. Likewise, the sperm count increased from 10.8 (3.51–21.6) to 20.3 (9.6–35) million. Notably, the percentage of rapid and slow sperms increased significantly from a median of 5% (0%–10%) and 15% (10 -20%) to a median of 10% (5%–15%) and 17.5% (15%–25%), respectively. The percentage of sperm with progressive movement increased from 35% (30%–40%) to 59% (45%–69%). The vitality of the sperms increased significantly as well. While the percentage of sperms with abnormal morphology decreased significantly at the end of follow-up. Conclusion: Our findings support the safety and efficacy of MSV in patients with clinically detectable varicocele. MSV has improved the semen parameters of the included patients, including sperm motility, volume, count, and total progressive motility, which may positively impact their fertility potential.